PENINGKATAN KINERJA USAHA MELALUI ANALISIS NET PROFIT MARGIN(NPM) - Moch Aminnudin; Hamdi Sari Maryoni (EKSYA : Jurnal Ekonomi Syariah, 2022)
This study aims to determine the increase in business performance through the analysis of Net Profit Margin (NPM) in Siti Snack's business. The research method used is a research method with quantitative analysis which tries to show the measurement of financial performance through NPM ratio analysis. The data used are secondary data originating from the financial statements of Siti Snack's business as the research sample for 2019. Based on the results of research and analysis of the financial performance assessment data of the "Siti Snack" NPM business, it can be seen that the values ​​produced each year fluctuate, if the value of the performance of this profitability indicator is compared with the average performance of the industry, the performance in 2019 to 2021 is found on average. the average is only 2.03% according to the standards imposed by Bank Indonesia, the financial performance of the institution is below standard. This can be caused by the tight business competition that occurs in the Jepara region, especially the snack food sector, and the Covid-19 virus factor that has hit Jepara for the last 2 years.